Intercultural rhetoric in higher education: The case of Iranian students' textual practices in North American graduate schools - Akbari Saneh, Nahal (University of Ottawa (Canada), 2009)
As part of their academic activities, English-as-a-Second-Language (ESL) graduate students in North American universities are expected to engage in a range of literacy practices of which writing is a major component. This study investigates the attitudes, perceptions and practices of five Iranian ESL students and the expectations of their professors in the context of disciplinary writing in higher education. In response to a recent call in the field of contrastive rhetoric for broadening the scope and revisiting the research methods in cultural studies of second language writing (Atkinson, 2004; Connor, 2004; Panetta, 2001), this qualitative inquiry is informed by a social theory of language (Bakhtin, 1986), a semiotic theory of culture (Lotman, 1990/2001), a situated literacies perspective of academic writing (Barton, Hamilton, & Ivanic, 2000), and a view of reasoning and argumentation as a socio-historic construct (Toulmin, 2001, 1964/2003). Data sources include text-based interviews with students, interviews with their professors, observation of tutoring sessions, and the analysis of textual artifacts as well as the written feedback provided on student writing. The findings point to a common perception of cultural differences between the textual practices of the students and those practices that are dominant in the context of their disciplines. The differences are discussed in terms of the educational background of the students, their past and present membership in various communities of practice, as well as a view of texts as historical constructs. The study further highlights some of the initial encounter experiences of the participating students in academic contact zones (Pratt, 1991), questioning the effectiveness of certain approaches that readers/evaluators adopt in responding to student writing. The research contributes to a re-conceptualization of the notion of culture in studies of second language writing, challenges the assumed homogeneity of argumentation as an academic literacy practice, and helps promote a dialogic view that is responsive to the textual practices of an increasingly diverse student population in North American academic settings.
Keywords: Education, Multilingual.; Education, Higher.